Design Of Mobile-Based Decoration Service E- Marketplace Application System - Andrayuga Mardhayiska, I Made; Adi Pramartha, Cokorda Rai (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2020)
Nowadays, people tend to search for goods or services through their mobile device using an electronic marketplace. In Bali, a decoration business for weddings, religious events, and other events grow rapidly. This business provides services that rents various kinds of decorations such as tents, chairs, tables, stages and others that are commonly used in ceremonial events. However, unfortunate for decoration service entrepreneurs who have high prospects, many of them are using the traditional method of marketing and sales such as word-of- mouth. Moreover, many of them not catching up with the current development of the e-market. By listing the services on the e-marketplace, easier for the customer to find the desired decoration services that fit their needs and budget. Also, by utilizing the e-marketplace will save the customer time, because the customer can just search, compare, and book to rent decorations without leaving home. The purpose of this research project is to create a mobile-based application of market place that accommodates entrepreneurs renting decorations. Our purposed mobile-based marketplace uses the prototyping method to build this mobile-based application.